Hilduin of Saint-Denis, the Passio S. Dionysii in prose and verse - Lapidge, Michael (Mittellateinische Studien und Texte, 2017)
Hilduin (c. 785-c. 860), abbot of Saint-Denis in Paris and archchaplain to Louis the Pious, was one of the leading scholars and administrators of the Carolingian empire. He was the first to translate the mystical Greek writings of the pseudo-Dionysius into Latin; he then identified this Dionysius with the first bishop of Paris of that name, and assigned his episcopacy and martyrdom to 96 A.D. Hilduin composed a life of St Dionysius in prose and verse: the prose work has not been edited since 1580, and the verse work - a major new Carolingian Latin poem - has never before been printed. Both texts are accompanied by facing-page English translation and detailed commentary; eleven appendices contain editions of the various texts on which Hilduin drew in compiling his fictitious account of St Dionysius.